Differentiation of key biomarkers in tea infusions using a target/nontarget gas chromatography/mass spectrometry workflow. (November 2018) - Kfoury, Nicole; Baydakov, Eugene; Gankin, Yuriy; Robbat, Albert
Abstract: Climatic conditions affect the chemical composition of edible crops, which can impact flavor, nutrition and overall consumer preferences. To understand these effects new data analysis software capable of tracking hundreds of compounds across years of samples under various environmental conditions is needed. Our recently developed mass spectral (MS) subtraction algorithms have been used with spectral deconvolution to efficiently analyze complex samples by 2-dimensional gas chromatography/mass spectrometry (GC-GC/MS). In this paper, we address the accuracy of identifying target and nontarget compounds by GC/MS. Findings indicate that Yunnan tea contains higher concentrations of floral compounds. In contrast, Fujian tea contains higher concentrations of compounds that exhibit fruity characteristics, but contains much less monoterpenes. Principal components analysis shows that seasonal changes in climate impact tea plants similarly despite location differences. For example, spring teas contained more of the sweet, floral and fruity compounds compared to summer teas, which had higher concentrations of green, woody, herbal compounds. Graphical abstract: Highlights: Comprehensive analysis of target and nontarget compounds in tea by GC/MS Deconvolution and MS subtraction of target and non-target compounds Seasonal metabolite differences in Yunnan and Fujian tea